If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -1(2 + 1i) * z + (-1 + 7i) = 0 Reorder the terms for easier multiplication: z + -1z(2 + 1i) + (-1 + 7i) = 0 z + (2 * -1z + 1i * -1z) + (-1 + 7i) = 0 Reorder the terms: z + (-1iz + -2z) + (-1 + 7i) = 0 z + (-1iz + -2z) + (-1 + 7i) = 0 Remove parenthesis around (-1 + 7i) z + -1iz + -2z + -1 + 7i = 0 Reorder the terms: -1 + 7i + -1iz + z + -2z = 0 Combine like terms: z + -2z = -1z -1 + 7i + -1iz + -1z = 0 Solving -1 + 7i + -1iz + -1z = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 7i + -1iz + 1 + -1z = 0 + 1 Reorder the terms: -1 + 1 + 7i + -1iz + -1z = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 7i + -1iz + -1z = 0 + 1 7i + -1iz + -1z = 0 + 1 Combine like terms: 0 + 1 = 1 7i + -1iz + -1z = 1 Add 'z' to each side of the equation. 7i + -1iz + -1z + z = 1 + z Combine like terms: -1z + z = 0 7i + -1iz + 0 = 1 + z 7i + -1iz = 1 + z Reorder the terms: -1 + 7i + -1iz + -1z = 1 + z + -1 + -1z Reorder the terms: -1 + 7i + -1iz + -1z = 1 + -1 + z + -1z Combine like terms: 1 + -1 = 0 -1 + 7i + -1iz + -1z = 0 + z + -1z -1 + 7i + -1iz + -1z = z + -1z Combine like terms: z + -1z = 0 -1 + 7i + -1iz + -1z = 0 The solution to this equation could not be determined.
| 3(d-0.8)=4x+4 | | -34+3x=18+5x | | 19.3-4.507= | | 5x-31=2x+8 | | x+73=3x+9 | | 1-a^2=x^2-2ax+1 | | -6(2t+6)=-12 | | 3r=-18 | | x=7y-47 | | 0.14y+0.07(y+6000)=1260 | | 12-3(4x+2)=3x+4(x-8) | | 3[x+5(6-x)+24]-11=79-15x | | 3-y=6y+7 | | 4(-18+24)= | | 2x-70=50+6x | | (-6+12i)(-7-9i)=0 | | 2x^3-3x=6x^2 | | 6r^2+12r+24=0 | | -(9-6a)-(10+5a)-14=-(2-6a)+(-a)+1 | | -5(n+4)+22=-3n-4 | | 15x-2(x+1)=154 | | 14x-4(4x-2)=5(2x+1)+3 | | 20.00-1.45*v=1.15 | | -9x-156=42-2x | | 14x-3(x+1)=96 | | 53=-16t^2+75t+30 | | 11x+9=4x+5 | | 4x^3+5x=13x^2 | | -[3x-(2x+6)]=-1-[3(2x-4)-3x] | | 8.12x+0.32=3.76x-3.23 | | 14x-3(x+1)=63 | | -10(s+3)=51 |